The Effect of Project-Based Learning by Utilizing the Canva Application to Increase the Interest in Learning History of Class X Students of Public Vocational High School 1 Seputih Agung - Dian Surya Virgawati; Risma Margaretha Sinaga; Novia Fitria Istiawati (MultiTech Publisher, 2024)
A psychological state known as interest in learning motivates someone to carry out learning activities. History subjects are considered boring so it is necessary to use a learning model that can attract students' interest and learning to history lessons. This study's goal was to clarify how project-based learning is used by utilizing the Canva application to increase student interest in learning history subjects. Experimental research is the approach used in this study. Class X students at public vocational high school 1 Seputih Agung, including 38 students altogether, are separated into two groups: the experimental class and the control class. There are two variables studied in the study, namely: (1) Project Based Learning by Utilizing Canva Application (2) Learning Interest. Data collection techniques provide questionnaires and tests to research samples and then process data through SPSS version 26.00 statistics. The average value between the pre-test results for the experimental class and the control class. before receiving treatment was 61.26 and 60.95, respectively, according to the study's findings. For the experimental class's average post-test results, the results were 72.11 and 64.11, respectively. Thus Project Based Learning by utilizing Canva has an effect on increasing interest in learning.